Pengaruh Kinerja Lingkungan Dan Kinerja Sosial Terhadap Kinerja Keuangan Dengan Good Corporate Governance Sebagai Variabel Pemoderasi - Luh Alin Kristiani; Desak Nyoman Sri Werastuti (Universitas Pendidikan Ganesha, 2020)
This study aims to determining the effect of environmental performance and social performance toward financial performance with good corporate governance as a moderating variable at service companies listed on the Indonesia Stock Exchange (IDX) for the period 2014-2018. This research is quantitative research using purposive sampling method. The type of data used in this study is secondary data obtained from annual reports and sustainability reports that are obtained indirectly through intermediaries or internet media. Data analysis in this research uses descriptive analysis, classic assumption test, multiple linear regression analysis, and Moderate Regression Analysis (MRA) using the SPSS 20.0 program. The results showed that; (1) environmental performance influences financial performance; (2) social performance influences financial performance; (3) Good Corporate Governance strengthens the effect of environmental performance on financial performance; (4) Good Corporate Governance weakens the effect of social performance on financial performance.